Meta-analysis Training as a Strategy to Accelerate the Publication Performance of AFEBSI East Java Members - Ananda Sabil Hussein; Raditha Dwi Vata Hapsari; Ida Yulianti; Rizka Zulfikar (Penerbit Goodwood, 2026)
Purpose: This community service program aims to improve lecturers' competence in meta-analysis techniques using JASP software as an open-source and user-friendly alternative to SPSS. Methodology: A hybrid training program totaling 16 instructional hours was employed, attended by 32 lecturers from 28 private universities in East Java. The training materials covered problem formulation, data extraction, summary effect estimation, heterogeneity testing, and publication-bias detection. Evaluation was conducted through pre-tests, post-tests, and post-training mentoring sessions. Results: The results showed a significant increase in the participants' knowledge from low to high. Most participants were able to independently perform all stages of the meta-analysis using JASP. The program outputs included 18 draft scientific articles that were ready for submission to reputable journals. Conclusions: JASP-based meta-analysis training is effective in enhancing private university lecturers’ capacity to conduct quantitative literature reviews and accelerate scientific publications. Limitations: This study has some limitations. JASP version 0.18.3 does not yet support three-level meta-analysis and network meta-analysis, which are increasingly being requested by tier-1 journals; therefore, collaboration with statisticians is still necessary for advanced topics. Contributions: This training model can be replicated to strengthen lecturers' research competence in other regions.